2008
DOI: 10.1007/s10452-008-9209-4
|View full text |Cite
|
Sign up to set email alerts
|

Mesozooplankton community in the Bay of Bengal (India): spatial variability during the summer monsoon

Abstract: This study addresses the spatial variability in mesozooplankton biomass and composition in the Central and Western Bay of Bengal (India) during the summer monsoon season of 2001. Perennially warmer sea surface temperatures ([28°C), stratified top layer (sea surface salinity, 28-33 psu), high turbidity, and low nutrient concentrations due to weak/null upwelling and light limitation make the Bay of Bengal a region of low primary productivity. Despite this, mesozooplankton biomass values, i.e. 2.9-104 mg C m -3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 52 publications
6
19
1
Order By: Relevance
“…a b d c Fig. 8 Distribution of a dissolved oxygen (μM), b nitrate (μM), c phosphate (μM) and d silicate (μM) in the Bay of Bengal during winter monsoon mer monsoon reports in order to understand its differential response to CE (Nair et al 1981;Muraleedharan et al 2007;Fernandes and Ramaiah 2009). It is found that the biovolume recorded in the SWBoB during winter monsoon 2005 was higher or sometimes comparable to the above reports (Table 1).…”
Section: Resultssupporting
confidence: 84%
“…a b d c Fig. 8 Distribution of a dissolved oxygen (μM), b nitrate (μM), c phosphate (μM) and d silicate (μM) in the Bay of Bengal during winter monsoon mer monsoon reports in order to understand its differential response to CE (Nair et al 1981;Muraleedharan et al 2007;Fernandes and Ramaiah 2009). It is found that the biovolume recorded in the SWBoB during winter monsoon 2005 was higher or sometimes comparable to the above reports (Table 1).…”
Section: Resultssupporting
confidence: 84%
“…Although the western Bay supports a higher mesozooplankton biomass (1.5 g C/m 2 ) in the upper 1,000 m during the fall intermonsoon, the number of copepod species was lower compared to the central transect (1.3 g C/m 2 , 170 species; Fernandes 2008). Nonetheless, the western transect is much richer in copepod species during this season than during summer (Fernandes and Ramaiah 2009). Notably, the generic and species compositions of copepods in general were quite similar to reports from the Arabian Sea by Madhupratap and Haridas (1990) and Madhupratap et al (2001).…”
Section: Depth Strata (M)supporting
confidence: 75%
“…Studies on mesozooplankton biomass, abundance, taxonomic groups, and ecology from the Bay of Bengal are few (Panikkar and Rao 1973;Nair et al 1981;Rakhesh et al 2006;Muraleedharan et al 2007;Fernandes 2008;Fernandes and Ramaiah 2009), and the information available is mostly for the upper 200 m. This investigation was carried out to provide a detailed account of spatial and vertical variations in the mesozooplankton biomass, density, and copepod assemblages in the upper 1,000 m in the western Bay of Bengal in an area that included two cold-core eddies along the sampling transect.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is supported by Shanthi and Ramanibai (2011) who reported that Calanoid copepods were most diverse group represented by 31 species in Chennai Coast (Cooum and Adyar), Bay of Bengal. Similarly, Fernandes and Ramaiah (2009) found that Calanoids were the predominant copepods in the Bay of Bengal which represents 132 species in a total of 163 species recorded.…”
Section: Species Composition and Diversity Of Copepodmentioning
confidence: 99%
“…In this biodiversity rich region, there are 126 species of phytoplankton and about 360 species of zooplankton (CMFRI, 1998) have been recorded. Copepods are one of the most broadly studied categories of marine zooplankton especially on the species composition and seasonal distribution in the Indian coastal waters (Sewell, 1929a;Krishnaswamy, 1950Krishnaswamy, , 1953Pillay, 1971;Madhupratap, 1979;Goswami, 1982;Sarkar et al, 1986;Mishra and Panigrahy, 1996;Padmavathi and Goswami, 1996;Ramaiah and Nair, 1997;Madhupratap, 1999;Perumal, 2003, 2005;Fernandes and Ramaiah, 2009;Sivaleela and Venkataraman, 2014). There are about 210 numbers of described families, 2,280 genera and more than 14,000 species of copepods recorded in the world.…”
Section: Introductionmentioning
confidence: 99%